Efficient numerical solution of micro–macro models for multicomponent transport and reaction problems in porous media. Issue 12 (13th August 2022) - Elbinger, T.; Knabner, P.
ABSTRACT: Transport and reaction of dissolved species in hierarchically structured complex media, e.g. porous media, can be described by micro–macro models (models with distributed micro-structure, F E 2 models). These models offer advantages compared to pure micro- or pure macroscale models but exhibit, compared to pure macroscale models, a strongly increased numerical complexity. We show how parallel computing together with Schur complement techniques can make those models numerically feasible.